Analyzed of Legal Siri Marriage Registration in a Population Administration (Family Card) a Study on Legal Protection for Children - Galluh Laraszaty; Syaiful Asmi Hasibuan; J.E.Melky Purba (Britain International for Academic Research (BIAR-Publisher), 2022)
Every marriage is not only based on biological needs between men and women who are recognized as legitimate, but as executor of the natural process of human life. Likewise, Islamic marriage law contains the main elements of a psychological and spiritual nature including inner and outer life, humanity, and truth. The formulation of the problem in this study is how the law on the registration of unregistered marriages into the population administration is a study of the analysis of legal protection for children. This research is a type of normative juridical research, using a law approach method. Basically, every marriage is recorded according to the applicable laws and regulations. This marriage registration is very important, because if it is not recorded, then the marriage is not recognized by the state and has certain legal consequences. Even though there are legal consequences if the marriage is not registered or in this case the siri marriage, because every resident must be recorded on the family card.